The effects of cashless payments on corruption - Goh, Yan Yin; Leong, Saw Hui; Pang, Meng Wei; Yew, Sin Kai; Yow, Zi Lin (2019)
The main purpose of this study is to examine the relationship between cashless payments and corruption in European countries from period of year 2000 to 2015. This is a secondary-based research whereby all the data is obtained from European Central Bank (ECB) data warehouse, with a total of 432 observations. This research examines empirically whether the corruption level is related to changes in Cashless Payments, Government Size, Democracy and Economic Prosperity. Generalized Method of Moments is adopted in this study to capture the effects of independent variables due to the fact that we used dynamic panel date in this research. The empirical result showed that both cashless payments and economic prosperity are significantly and negatively correlated to corruption. On the other hand, government size and democracy are found to be significantly and positively correlated to corruption. This research allows the government to understand the variables that may impact corruption level. Thus, this research is useful for the government in choosing the method of cashless transaction to focus on in bringing down the rate of corruption.